STATE-OWNED ENTERPRISE LAW IN THE PERSPECTIVE OF GOOD CORPORATE GOVERNANCE: A LITERATURE ANALYSIS OF THE MANAGEMENT, SUPERVISION, AND ACCOUNTABILITY OF STATE-OWNED ENTERPRISES AS INSTRUMENTS OF NATIONAL DEVELOPMENT AND PROFIT-ORIENTED ECONOMIC ENTITIES — A LITERATURE REVIEW - Shohib Muslim; Hadenan Towpek; Mohd Syahrin (INJOSEDU: International Journal of Social and Education, 2026)
State-Owned Enterprises (SOEs) occupy a strategic position as instruments of national development and profit-oriented economic entities, making good governance a key prerequisite for realising this dual function. This study is a literature review that analyses SOE law from the perspective of Good Corporate Governance (GCG), focusing on the aspects of SOE management, supervision and accountability. Through a normative literature analysis of Law No. 19 of 2003 on SOEs, KNKG guidelines, and OECD GCG principles, this study identifies that the formal structure of SOE organs is in line with the principle of separation of functions, but the practice of organ appointment, political intervention, and weak supervisory independence remain major obstacles. SOE accountability requires the integration of public and private law norms, with the business judgement rule and fiduciary duty principles as pillars of legal protection for the Board of Directors as well as a guarantee of state interests. In conclusion, strengthening GCG through regulatory reform, professionalisation of management bodies, and external oversight synergy is necessary to ensure that SOEs can carry out their dual roles effectively and sustainably.